FORMING A CULTURE OF HEALTHY LIFESTYLE AMONG STUDENTS IN A DIGITAL EDUCATIONAL ENVIRONMENT (BASED ON PRIMARY SCHOOL STUDENTS) (European Journal of Interdisciplinary Research and Development, 2025)
This article analyzes the pedagogical possibilities and practical directions of forming a culture of healthy lifestyle among primary school students in a digital educational environment. In the context of the deep integration of digital technologies into the educational process, it is substantiated that healthy lifestyle skills can be effectively instilled in children not only through traditional methods but also through the use of interactive digital resources. Based on observations and surveys conducted among primary school students, the research highlights effective methods of teaching elements of a healthy lifestyle through digital games, video lessons, and applications focused on healthy habits. The article also examines the role of digital tools in increasing students' physical activity, ensuring hygiene, promoting nutritional culture, and supporting psychological well-being. The conclusion recommends the integration of digital education and healthy lifestyle promotion as an innovative approach in primary education.